Age matters: Life-stage, tissue, and sex-specific gene expression dynamics in Ips typographus (Coleoptera: Curculionidae: Scolytinae) - Naseer, Aisha; Mogilicherla, Kanakachari; Sellamuthu, Gothandapani; Roy, Amit (Frontiers in Forests and Global Change, 2023)
The Eurasian spruce bark beetle (ESBB), Ips typographus, has recently caused catastrophic damage to Norway spruce (Picea abies) forests in Europe, resulting in the loss of more than 100 million cubic meters of wood. Traditional forest management strategies have failed to constrain the growing infestation rate; hence, novel measures must be deployed. A better understanding of ESBB physiology and adaptation to host allelochemicals may provide a platform for future management strategies using molecular tools such as RNA interference. To understand ESBB physiology and adaptation, the current study unravelled the gene expression dynamics in different life stages and tissues of ESBB. We obtained ESBB transcriptomes for different life stages [larvae (L1, L2, and L3), pupa, callow, and adult] and male/female tissues (gut, fat body, and head) from callow and adult beetles. Differential gene expression analysis (DGE) identified multiple gene families related to detoxification, digestion, resistance, and transport in different life stages and tissues of the beetle. Gene Ontology (GO) enrichment revealed 61 critical metabolic pathways enriched across all DGE comparisons. DGE analysis further pinpoints the differential expression of essential genes involved in detoxification, digestion, transport, and defence in various tissues and life stages. RT-qPCR experiments and enzymatic assays corroborated the findings further. The catalogue of differentially expressed genes identified in ESBB could aid a better understanding of ESBB physiology and adaptation to the host and serve as targets for future RNAi-based ESBB management.